2018
DOI: 10.1002/jmri.26040
|View full text |Cite
|
Sign up to set email alerts
|

4D flow MRI quantification of mitral and tricuspid regurgitation: Reproducibility and consistency relative to conventional MRI

Abstract: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1147-1158.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 40 publications
6
62
0
2
Order By: Relevance
“…A systematic review of 4D flow-derived methods for MR quantification identified seven studies that demonstrated that 4D flowderived MR volume is similar to that derived using standard CMR methods and even to that derived using 3D transoesophageal echocardiography (TOE) methods 29 . In one study, a standard CMR method for quantification of MR volume and 4D flow-derived methods yielded similar results 30 .…”
Section: Cine Imagesmentioning
confidence: 87%
“…A systematic review of 4D flow-derived methods for MR quantification identified seven studies that demonstrated that 4D flowderived MR volume is similar to that derived using standard CMR methods and even to that derived using 3D transoesophageal echocardiography (TOE) methods 29 . In one study, a standard CMR method for quantification of MR volume and 4D flow-derived methods yielded similar results 30 .…”
Section: Cine Imagesmentioning
confidence: 87%
“…In addition, the multicenter reproducibility and test–retest reliability of 4D flow is another important aspect for its clinical applications and longitudinal investigations as well. Good reproducibility and low interobserver variability has been demonstrated for 4D flow MRI in the application of aorta, intraheart, intracranial arteries, and portal venous system . However, such investigation in the neurovascular system is still limited, especially for cerebral arteries.…”
mentioning
confidence: 99%
“…After substraction of the forward volume measured in the pulmonary artery from the total RV stroke volume assessed by RV volumetry (ciné steady-state free precession imaging), absolute TR regurgitant volume and fraction can be calculated (59). More recently, 4D-flow CMR has been used for 3D quantification of TR and can correct for through-plane motion as well as eccentricity, with high intra-and interobserver reproducibility and high consistency with 2D phase contrast velocity mapping and echocardiography (60,61).…”
Section: Regurgitant Volumementioning
confidence: 99%